Synthesis and Macrodomain Binding of Mono‐ADP‐Ribosylated Peptides. Issue 36 (28th July 2016) - Kistemaker, Hans A. V.; Nardozza, Aurelio Pio; Overkleeft, Herman S.; van der Marel, Gijs A.; Ladurner, Andreas G.; Filippov, Dmitri V.
Abstract: Mono‐ADP‐ribosylation is a dynamic posttranslational modification (PTM) with important roles in signaling. Mammalian proteins that recognize or hydrolyze mono‐ADP‐ribosylated proteins have been described. We report the synthesis of ADP‐ribosylated peptides from the proteins histone H2B, RhoA and, HNP‐1. An innovative procedure was applied that makes use of pre‐phosphorylated amino acid building blocks. Binding assays revealed that the macrodomains of human MacroD2 and TARG1 exhibit distinct specificities for the different ADP‐ribosylated peptides, thus showing that the sequence surrounding ADP‐ribosylated residues affects the substrate selectivity of macrodomains. Abstract : Ties that bind : The synthesis of a number of mono‐ADP‐ribosylated peptides is described. Binding studies of these peptides with different macrodomains showed that the peptide fragment surrounding the ADPr modification influences the binding properties.